P‐41: Reduction and Mechanism of MOD‐Contact ESD Failure in a‐Si Product Containing PLN. Issue 1 (28th June 2021) - Zhang, Xia; Liang, Yuheng; Li, Lanyan; Liu, Gang; Hsieh, Chung-Ching; Xiao, Juncheng; Zhao, Bin
Abstract : In this paper, it is found that the residual of Multi Layer is the citical factors Lead to the failure of MOD contact ESD test, The cause of residual during Laser cut has been anaysised, and the mechanism has been studied, furthermore, several improvement methods has been proposed.